IRF2BP2 Reduces Macrophage Inflammation and Susceptibility to Atherosclerosis. Issue 8 (25th September 2015) - Chen, Hsiao-Huei; Keyhanian, Kianoosh; Zhou, Xun; Vilmundarson, Ragnar O.; Almontashiri, Naif A.M.; Cruz, Shelly A.; Pandey, Nihar R.; Lerma Yap, Nida; Ho, Tiffany; Stewart, Chloe A.; Huang, Hua; Hari, Aswin; et al.
<x xml:space="preserve">Abstract</x> Rationale: Inflammation impairs macrophage cholesterol clearance from vascular tissues and promotes atherosclerosis. Inflammatory macrophages suppress expression of the transcription cofactor interferon regulatory factor 2–binding protein 2 (IRF2BP2), and genetic variants near IRF2BP2 associate with ischemic heart disease progression in humans. Objectives: To test whether IRF2BP2 in macrophages affects atherosclerosis in mice and humans. Methods and Results: We generated mice that delete IRF2BP2 in macrophages. IRF2BP2-deficient macrophages worsened atherosclerosis in irradiated low-density lipoprotein receptor null-recipient mice and in apolipoprotein E null mice. IRF2BP2-deficient macrophages were inflammatory and had impaired cholesterol efflux because of their inability to activate the cholesterol transporter ABCA1 in response to cholesterol loading. Their expression of the anti-inflammatory transcription factor Krüppel-like factor 2 was markedly reduced. Promoter studies revealed that IRF2BP2 is required for MEF2-dependent activation of Krüppel-like factor 2. Importantly, restoring Krüppel-like factor 2 in IRF2BP2-deficient macrophages attenuated M1 inflammatory and rescued M2 anti-inflammatory gene activation and improved the cholesterol efflux deficit by restoring ABCA1 activation in response to cholesterol loading. In a cohort of 1066 angiographic cases and 1011 controls, homozygous carriers of a deletion polymorphism (rs3045215) in the 3′ untranslated region sequence of human IRF2BP2 mRNA had a higher risk of coronary artery disease (recessive model, odds ratio [95% confidence interval]=1.560 [1.179–2.065], P=1.73E-03) and had lower IRF2BP2 (and Krüppel-like factor 2) protein levels in peripheral blood mononuclear cells. The effect of this deletion polymorphism to suppress protein expression was confirmed in luciferase reporter studies. Conclusion: Ablation of IRF2BP2 in macrophages worsens atherosclerosis in mice, and a deletion variant that lowers IRF2BP2 expression predisposes to coronary artery disease in humans.